Jurisdição especial do Tribunal de Contas - Dantas, Fábio Wilder da Silva (2016)
This monograph endeavors to study the legal status of the decisions made by the Court of Accounts in Brazil, inquiring the hypothesis that accountability in Brazil, when proceeded through the legal process of judgement of accounts, consists in a special administrative justice, outside of the Judiciary Branch of Power, as an exception to the system of judicial jurisdiction established in the 5th article, section XXXV, of the Federal Constitution of Brazil. Chapter one examines the history of public accountability and the creation of the Court of Accountability in Brazil. The second chapter examines the nature of jurisdiction, commenting the work of the most important authors that addressed the issue. The third chapter reviews the bibliography on the discussion of the subject, considering the context of various Constitution drafts occurred since 1891 in Brazil. Finally, on the forth chapter the main arguments concerning the legal status of the decisions made by the Court of Accounts in Brazil are described and discussed.